Metagenomic Comparison of Gut Microbes of Lemur catta in Captive and Semi-Free-Range Environments - Chunzhong Xu; Xinzi Guo; Lian Li (Animals)
In order to protect endangered species, many zoos adopt diverse rearing models to achieve optimal conservation outcomes. This study employed metagenomic approaches to assess differences in the fecal microbiome of captive and semi-free-ranging ring-tailed lemurs (Lemur catta). The results show that captivity significantly altered the microbial community structure. The inter-individual variability in the microbial community within the captive-bred (CB) group was lower than that in the semi-free-ranging (FR) group, yet these individuals harbored a higher abundance of potential pathogens (Treponema_D). In contrast, microbial genera associated with fiber degradation and short-chain fatty acid production in the FR group were significantly elevated (Faecalibacterium, Roseburia, and Megamonas) as compared to the CB group. Environmental variations between the two rearing systems led to distinct profiles in microbial functions and carbohydrate-active enzyme gene composition. Notably, the FR group of lemurs exhibited an increased abundance of enzyme genes associated with the degradation of complex polysaccharides (cellulose, hemicellulose, and pectin), suggesting that their diet, rich in natural plant fibers, enhances the capacity of their gut microbiota to extract essential energy and nutrients. Conversely, the CB group displayed a more homogeneous microbial community with a higher prevalence of potential pathogens, implying that a captive lifestyle may negatively impact gastrointestinal health. These findings offer valuable insights into the influence of rearing conditions on gut microbial ecology and its potential implications for the health management of ring-tailed lemurs.